2017
DOI: 10.1111/cen.13347
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of PHEX, FGF23 and CLCN5 in patients with hypophosphataemic rickets

Abstract: Novel and de novo mutations are frequent and PHEX mutations are still the most common genetic defects in the Turkish population. Gene copy number analysis should be considered in patients with negative results by conventional PCR-based sequencing analysis. The current study further expands the mutation spectrum underlying HR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
17
0
4
Order By: Relevance
“…More than 220 CLCN5 pathogenic mutations have been reported so far. Mutations were found scattered along all exons of the gene and in different protein domains [9,[34][35][36][37][38][39][40][41][42][43][44][45]. Mansour-Hendili et al [9] reported that the majority were missense and frameshift mutations (33.33% and 29.05% respectively) followed by nonsense mutations (17.52%), splicing mutations (12.39%), and large deletions (4.70%).…”
Section: Discussionmentioning
confidence: 99%
“…More than 220 CLCN5 pathogenic mutations have been reported so far. Mutations were found scattered along all exons of the gene and in different protein domains [9,[34][35][36][37][38][39][40][41][42][43][44][45]. Mansour-Hendili et al [9] reported that the majority were missense and frameshift mutations (33.33% and 29.05% respectively) followed by nonsense mutations (17.52%), splicing mutations (12.39%), and large deletions (4.70%).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of XLH is based on the association of clinical, radiological and biochemical findings (Box 1). In patients with a negative family history (approximately one-third of reported patients 31,32 ), mutational analysis of the PHEX gene is recommended, which can provide negative or positive confirmation in ~70-90% of cases 31,[33][34][35][36][37][38][39][40][41][42][43] . Specific molecular genetic defects such as large deletions, deletions removing pseudo-exons of PHEX or mosaicism can be difficult to identify 44,45 .…”
Section: Harrison's Groovementioning
confidence: 99%
“…These mutations affect the production of the α1/α2 chains of type 1 collagen, an important structural component of the bone, skin, tendons, ligaments, and other connective tissues [44]. Animal studies have also observed muscle weakness in OI mice [45], providing additional evidence for the muscle abnormalities in OI. The exact mechanisms leading to muscle weakness are yet unclear but they can be result of intrinsic muscle factors or direct paracrine effects of the abnormal bone matrix (i.e., increased TGF-β signaling in OI decreases lean mass).…”
Section: Human and Animal Bone-focused Knock-out “Models” Comprising mentioning
confidence: 99%